Processes controlling the distributions and cycling of dissolved aluminum and manganese in the northeastern Indian Ocean - Yang, Yichao; Li, Lei; Ren, Jingling; Jiang, Shuo; Zhang, Jing (Frontiers in Marine Science, 2023)
Aluminum and manganese are both key parameters in the GEOTRACES program. Data on dissolved aluminum (dAl) and dissolved manganese (dMn) relative to their geochemical behavior remain limited in the northeastern Indian Ocean (IO; including the Bay of Bengal (BoB) and equatorial Indian Ocean (Eq. IO)). Seawater samples collected in the BoB and Eq. IO during the spring inter-monsoon period (7 March to 9 April) of 2017 were analyzed to investigate the behavior and main processes controlling the distributions of dAl and dMn in the northeastern IO. The average concentrations of dAl and dMn in the mixed layer of the BoB were 16.6 and 6.7 nM, respectively. A modified 1-D box-model equation was utilized to estimate the contributions of different sources to dAl and dMn in the mixed layer. Al released from the desorption of and/or dissolution of the lithogenic sediments discharged by the Ganga–Brahmaputra (G-B) river system predominantly controlled the dAl distributions in the mixed layer of the BoB, while the desorption from the lithogenic sediments only contributed approximately 13%–21% dMn. Additional dMn input from the advection of Andaman Sea water and photo-reduction–dissolution of particulate Mn(IV) contributed more than 60% dMn in the mixed layer of the BoB. dAl and dMn in the surface mixed layer of the Eq. IO were mainly affected by the mixing of dAl- and dMn-enriched BoB surface water and low-dAl, low-dMn southern Arabian Sea surface water. Considering water mass properties and dAl concentrations, the distributions of dAl in the intermediate water (750–1,500 m) of northeastern IO were controlled by the mixing of Red Sea Intermediate Water, Indonesian Intermediate Water, and intermediate water of the BoB. Different from dAl, the apparent oxygen utilization relationship with dMn concentrations indicated that the regeneration of lithogenic particles under hypoxic conditions played a more important role than the remineralization of settling organic particles in controlling dMn distributions in the subsurface and intermediate water body (100–1,000 m) of the BoB and that remineralization of biogenic particles mattered to dMn in the subsurface of the Eq. IO.